Beispiel Nr: 04
$\text{Gegeben:} \\ \text{Ebene1: } \vec{x} =\left( \begin{array}{c} a1 \\ a2 \\ a3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} b1 \\ b2 \\ b3 \\ \end{array} \right) + \sigma \left( \begin{array}{c} c1 \\ c2 \\ c3 \\ \end{array} \right) \\ \text{Ebene2: } n1 x_1+n2 x_2+n3 x_3+k1=0 \\ \\ \text{Gesucht:} \\\text{Lage der Ebenen zueinander} \\ \\ \textbf{Gegeben:} \\ \text{Ebene1: } \vec{x} =\left( \begin{array}{c} 2 \\ 3 \\ 2 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 1 \\ -2 \\ 1 \\ \end{array} \right) + \sigma \left( \begin{array}{c} 5 \\ 3 \\ 1 \\ \end{array} \right) \\ \text{Ebene2: } 5 x_1-4 x_2-13 x_3+28=0 \\ \\ \\ \textbf{Rechnung:} \\ \text{Ebene: } \vec{x} =\left( \begin{array}{c} 2 \\ 3 \\ 2 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 1 \\ -2 \\ 1 \\ \end{array} \right) + \sigma \left( \begin{array}{c} 5 \\ 3 \\ 1 \\ \end{array} \right) \\ \text{Ebene: } 5 x_1-4 x_2-13 x_3+28=0 \\ \begin{array}{cccc} x_1=& 2 &+1\lambda &+5\sigma \\ x_2=&3 &-2\lambda &+3\sigma \\ x_3=&2 &+1\lambda &+3\sigma\\ \end{array} \\ 5( 2+1\lambda+5\sigma) -4(3-2\lambda+3\sigma) -13 (2+1\lambda+1\sigma)+28=0 \\ 0\lambda+0\sigma+0=0 \\ \\ 0=0 \\\\ \text{Ebenen sind identisch} $